Case Report: A case of HNF1B mutation patient with first presentation of diabetic ketosis - Ge, Shenghui; Yang, Mengge; Gong, Wenfeng; Chen, Wenzhe; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2022)
Background: Maturity-onset diabetes of the young 5 (MODY5), a rare diabetes syndrome of young adults, is associated with variants in hepatocyte nuclear factor 1B (HNF1B) gene. Case Presentation: We report a case of MODY5, which presented with diabetic ketosis, multiple renal cysts, and hypokalemia. In this case, the HNF1B score was estimated as 13 and a heterozygous variant of HNF1B in exon 4 (c.826C>T, p.Arg276*) was identified through Sanger sequencing. Conclusions: Multiple renal cysts and youth-onset diabetes are common manifestations in patients with HNF1B mutations, and pancreatic islet reserve insufficiency may be a potential cause of diabetic ketosis in MODY5.